ANALISIS PENGEMBANGAN FASILITAS SISI UDARA BANDAR UDARA AHMAD YANI SEMARANG - , EKO PRANOWO, Ir. Wardhani Sartono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The air transportation has rapidly grown these recent days, however, the growth itself has not been suitable with the need required. This research is made to find what facilities are still needed in Ahmad Yani airport in Semarang compared to the facilities of the airport has now. This research is focused on airport facilities of Ahmad Yani Airport in Semarang. This research calculates the capacity of Ahmad Yani Airport's taxiway, runway, and apron and estimates the need of the airport's airside facilities based on its capacity now for it is used in planning year. The passanger growth of Ahmad Yani Airport is made using econometric method and per route proportion, hereforth, the result of the passanger growth calculation is converted into the aircraft number serving in Ahmad Yani Airport in Semarang. The runway calculation is made using several methods, they are FAA(Federal Aviation Administration) method, analitical method, and empirical method. While the taxiway calculation is calculated using FAA and JICA methods, the apron calculatian uses JICA method by considering consiously the static and dinamic capacity inside the airport's apron. The results of data analysis find that, now, Ahmad Yani Airport, using empiric method, is able to serve 10 aircraft movements/ hour for critical aircraft B 737 900. using analitical method, its runway capacity now is able to take 43 movements/ hour, while using FAA method, the runway capacity reaches 100 monement/ hour. Further, for the existing apron capacity in Ahmad Yani Airport in Semarang has only been able to shelter 1 plane. Therefore, based on the airport's growth, Ahmad Yani Airport in Semarang needs to develope its airside facilities for runway capacity up to 20 movements/ hour, apron capacity up to 12 aircrafts/ hour, and taxiway capacity up to 20 movements/ hour. In the conclusion, the airside facilities of Ahmad Yani Airport are that the taxiway component is able to hold up to year of 2030, the runway component needs free up by building paralel taxiway to increase runway capacity, and the apron needs width up to 450m x 110m to to be able to shelter 12 aircraft at once.